The effectiveness of broccoli and gotu cola extract combination (Brogandi) on executive function and memory in nursing students - Dinda Sylvania Raisa; Lisna Anisa Fitriana; Irma Darmawati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Nursing students face high academic and clinical practice demands that can potentially affect cognitive function, particularly executive function and working memory. The combination of broccoli and gotu cola extracts (Brogandi) is thought to support cognitive function through neuroprotective mechanisms. Purpose: To analyze the effectiveness of Brogandi on the executive function and memory of nursing students compared to a non-herbal and control group. Method: A quasi-experimental non-equivalent control group pre-post test design was used on 60 students, divided into three groups: herbal (Brogandi, 2×1000 mg/day), non-herbal (multivitamins with cognitive function enhancement claims; 1 capsule/day), and control. Measurements were taken before and after a 4-week intervention using the Five-Point Test, Trail Making Test B, and Backward Digit Span. Results: Within the group, the Brogandi group showed an increase in the Unique Design FPT and BDS and a decrease in TMT-B time (p<0.05) with varying effect sizes. The non-herbal group also showed an increase in the Unique Design FPT and a decrease in TMT-B time (p<0.05), while the control group showed improvement in TMT-B (p<0.05). Comparison of changes (Δ post–pre) between groups showed significant differences in Unique Design FPT (p<0.001); post-hoc showed that the Brogandi and non-herbal groups were significantly different from the control group, but not from each other. Conclusion: Brogandi for 4 weeks showed domain-specific effects with pre–post improvements in figural fluency, working memory, and set-shifting. However, intergroup differences were only apparent in figural fluency, with an advantage over the control but no significant difference compared to the active multivitamin comparator. Further research should use a placebo-controlled randomized trial design with equalization of regimens between groups to reduce non-specific biases and strengthen findings.